2018
DOI: 10.1016/j.bjm.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cryopreservation of basidiomycetes

Abstract: Basidiomycetes have several biotechnological and industrial applications such as enzyme production, bioremediation, pharmaceutical and functional food production. Due to climatic features, the preservation of several basidiomycetes is threatened, and to guarantee the preservation of this genetic resource, the development of long-term preservation techniques is necessary once there is no universal protocol for the cryopreservation of basidiomycetes. Cryopreservation is a technique in which microorganisms are su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 66 publications
(112 reference statements)
1
15
0
1
Order By: Relevance
“…cereal grains in mycelial viability cryopreservation, probably because grains provide an internal capillary net, besides protectant substances, which works as a physical protection to mycelia, confirming the reports of Tanaka et al [17] and Mata and Pérez-Merlo [26]. Another aspect is that glycerol addition to the substrate in order to obtain a Bpreservation substrate^ [22] was not effective to keep the mycelial viability in all treatments after 5-year cryopreservation. The association of the semisolid culture medium was effective to recover the mycelial viability only when wheat or rye grains were used for mycelial growth, without glycerol addition to the substrate, and with glycerol addition to the cryotube.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…cereal grains in mycelial viability cryopreservation, probably because grains provide an internal capillary net, besides protectant substances, which works as a physical protection to mycelia, confirming the reports of Tanaka et al [17] and Mata and Pérez-Merlo [26]. Another aspect is that glycerol addition to the substrate in order to obtain a Bpreservation substrate^ [22] was not effective to keep the mycelial viability in all treatments after 5-year cryopreservation. The association of the semisolid culture medium was effective to recover the mycelial viability only when wheat or rye grains were used for mycelial growth, without glycerol addition to the substrate, and with glycerol addition to the cryotube.…”
Section: Resultssupporting
confidence: 80%
“…For the 5-year cryopreservation at − 70°C of A. subrufescens, the fungal growth in whole grains of hard endosperm wheat or rye is recommended, even though MEA and potato dextrose agar disks were broadly used in the basidiomycete cryopreservation [22]. Colauto et al [12] reported effective mycelial viability recovery of A. subrufescens grown in whole grains of rice with hulls and cryopreserved at − 86°C for 1 year with 10% glycerol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations